2008
DOI: 10.1007/s11357-008-9054-3
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and longevity in birds

Abstract: The links between energy expenditure and ageing are different at different levels of enquiry. When studies have examined the relationships between different species within a given class the association is generally negative-animals with greater metabolism per gram of tissue live shorter lives. Within species, or between classes (e.g. between birds and mammals) the association is the opposite-animals with higher metabolic rates live longer. We have previously shown in mammals that the negative association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 113 publications
0
42
0
Order By: Relevance
“…This idea became the 'rate of living' theory (Pearl, 1928), an idea that dominated ageing research for more than 50 years. The 'rate of living theory' has been repeatedly disproven, for example by observations that birds and bats combine long lives with high rates of metabolism (Austad and Fischer, 1991;Brunet-Rossinni and Austad, 2004;Holmes and Austad, 1994;Holmes et al, 2001;Furness and Speakman, 2008), the demonstration that if total energy expenditure is multiplied by lifespan rather than RMR the result is no longer independent of body size (Speakman, 2005), and the observation that when individual lifespans are compared within species, rather than comparing lifespans across species, it turns out the ones with higher metabolism live longer (Speakman et al, 2004b).…”
Section: Resting Metabolic Rate (Rmr)mentioning
confidence: 99%
“…This idea became the 'rate of living' theory (Pearl, 1928), an idea that dominated ageing research for more than 50 years. The 'rate of living theory' has been repeatedly disproven, for example by observations that birds and bats combine long lives with high rates of metabolism (Austad and Fischer, 1991;Brunet-Rossinni and Austad, 2004;Holmes and Austad, 1994;Holmes et al, 2001;Furness and Speakman, 2008), the demonstration that if total energy expenditure is multiplied by lifespan rather than RMR the result is no longer independent of body size (Speakman, 2005), and the observation that when individual lifespans are compared within species, rather than comparing lifespans across species, it turns out the ones with higher metabolism live longer (Speakman et al, 2004b).…”
Section: Resting Metabolic Rate (Rmr)mentioning
confidence: 99%
“…The considerable gap between the maximum sustained working level of 4 or 5 times BMR that hard-working parent birds are prepared to give (Drent and Daan, 1980) and the physiological maxima of 7-10 times BMR that can be achieved under exceptional conditions makes evolutionary sense if working hard comes at a survival cost (Valencak et al, 2009). My reading of the literature suggests that any kind of hard work, perhaps above taxon-(or rather, ecology-) dependent thresholds (Speakman et al, 2002;Speakman, 2005;Furness and Speakman, 2008), comes with wear and tear. A precipitous increase in the likelihood of organ or performance failure, and mortality associated with increases in energy expenditure (Ricklefs, 2008), would explain why animals are reluctant to habitually spend as much as they are physiologically capable of (Valencak et al, 2009); that is, if such precipitous increases the likelihood of death are not compensated for by increases in reproductive output (Williams, 1966;Lessells, 1991;Daan and Tinbergen, 1997).…”
Section: Protecting Long-term Fitness Assets: the Evolution Of Lazinessmentioning
confidence: 99%
“…In the empirical literature, metabolic rate, and more specifically resting metabolic rate (RMR) and the more strictly defined basal metabolic rate, has been related to lifespan across a number of animal species (Schmidt-Nielsen, 1984;Furness and Speakman, 2008). However, a difficulty with this relationship is that both metabolic rate and lifespan correlate strongly with body mass and it is therefore not clear whether metabolic rate has any causal role in the relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, mass-independent metabolic rates should be calculated as residuals from a linear regression between metabolic rate and body mass. Studies using such residual metabolic rates have found no correlation between metabolic rate and lifespan across vertebrate species (Speakman, 2005;de Magalhães et al, 2007;Furness and Speakman, 2008).…”
Section: Introductionmentioning
confidence: 99%